The Art in Introducing Self: I am … rrr… - Wicaksono, Julien Arief; Taufan, Gullit Tornado (Politeknik Negeri Jember, 2019)
This study analyzed the distinctive categories used in describing oneself written in English by second semester Indonesian students of non-English department, namely agriculture. They are found to be categorized as: 1) name; 2) hometown; 3) character and physical appearance; 4) favourite food, beverages or activity; 5) age; and 6) academic information. In findings, the students tended to mention their unseen aspects rather than their physical appearance which are actually more important and easy to be noticed.Keywords: describing, introducing oneself, non-English students.